Estrogen induces c-Kit and an aggressive phenotype in a model of invasive lobular breast cancer. (November 2017) - Harrell, J.; Shroka, Thomas; Jacobsen, Britta
Abstract Among the molecular subtypes of breast cancer are luminal (A or B) estrogen receptor positive (ER+), HER2+, and triple negative (basal-like). In addition to the molecular subtypes, there are 18 histologic breast cancer subtypes classified on appearance, including invasive lobular breast carcinoma (ILC), which are 8–15% of all breast cancers and are largely ER+ tumors. We used a new model of ER+ ILC, called BCK4. To determine the estrogen regulated genes in our ILC model, we examined BCK4 xenograft tumors from mice supplemented with or without estrogen using gene expression arrays. Approximately 3000 genes were regulated by estrogen in vivo. Hierarchical cluster analyses of the BCK4 derived tumors compared with ER+ and ER- breast cancer cell lines show the estrogen treated BCK4 tumors group with ER- breast cancers most likely due to a high proliferation score, while tumors from cellulose supplemented mice were more related to ER+ breast tumor cells. To elucidate genes regulated in vitro by estrogen in BCK4 cells, we performed expression profiling using Illumina arrays of the BCK4 cell line, treated with or without estrogen in vitro. A set of ~200 overlapping genes were regulated by estrogen in the BCK4 cell line and xenograft tumors, and pathway analysis revealed that the c-Kit pathway might be a target to reduce estrogen-induced proliferation. Subsequent studies found that inhibition of c-Kit activity using imatinib mesylate (Gleevec®) blocked estrogen mediated stimulation of BCK4 tumors and BCK4 cells in vitro as effectively as the anti-estrogen fulvestrant (Faslodex®). Decreased expression of c-Kit using shRNA also decreased baseline and estrogen induced proliferation in vitro and in vivo. These studies are the first to indicate that c-Kit inhibition is an effective approach to target c-Kit+ ILC.